PENGUATAN GERAKAN MEMILAH SAMPAH MELALUI TOKEN EKONOMI, PROMPTING DAN PSIKOEDUKASI PENGELOLAAN SAMPAH DOMESTIK - Lusy Asa Akhrani; Dewi Puri Astiti; Inesha Febrina Setiajid; Nabila Khairanti; Muh. Mughny Mehdiviky (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Kampung Payung is a themed village located on Jalan LA Sucipto in Pandanwangi Village, Blimbing District, Malang City. The community's awareness and concern for waste disposal is still very low. People frequently dump garbage into rivers, and many others burn garbage, do not sort waste, and pile it up. The intervention in 2020 resulted in the formation of a community that cares about the environment and initiated the behavior of sorting waste from inside the house for 17 community members out of a total of 60 residents of RW 03. However, after two years, the behavior of sorting waste decreased and the behavior of throwing garbage in the community worsened. In 2022, community intervention aims to strengthen and improve waste sorting behavior for dasawisma members who have been sorting waste in their respective homes by using token economy, prompting, and psychoeducation methods to increase knowledge of domestic waste management and strengthen environmental care communities. The program participants were 9 women from Dasawisma Kampung Payung who were chosen based on their willingness to participate in the behavior and community strengthening program. Data collection methods include surveys, documentation, interviews, and observations. The behavior change technique uses behavior modification techniques such as economic tokens and prompting, whereas knowledge change is accomplished through psychoeducation, which is assessed via pretest and posttest. According to the findings of the intervention, economic tokens, prompting, and psychoeducation have been shown to strengthen waste sorting behavior and increase participants' knowledge of waste sorting behavior.